MEDICAL STUDENT’S MENTAL HEALTH: COPING STRATEGIES THAT WORK (AND DON’T) - Widyadhana, Amanda; Rochmanti, Maftuchah (jfpublisher, 2025)
Introduction. Stress, anxiety, and depression are common forms of mental health disorders faced by medical students worldwide. These disorders can lead to depression, anxiety, burnout as well as suicidal ideation and attempts. Coping strategies can help students face psychological distress, either through problem-focused coping, emotion-focused coping, or dysfunctional coping. This review aims to provide the prevalence of stress, anxiety, and depression in medical students, along with effective coping strategies to combat these mental health conditions. Method. This review utilized Google Scholar, PubMed, and Scopus to review articles in English and Indonesian. Various keywords were used, such as